Computational Insights in Identification of Proficient Transient Receptor Potential Vanilloid 1 Inhibitors: A Pathway for Extenuating Chemotherapy-Induced Peripheral Neuropathy - Dinesh Kumar Chandanapalli; Shristi Arya; Shailesh Mani Tripathi; Ashish Kumar; Arbaz Sujat Shaikh; Venkata Rao Kaki; Sandeep Sundriyal; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Sequential development of pathological changes in relation to bacterial loads, apoptosis, and immune responses in experimental infection of Streptococcus dysgalactiae subsp. equisimilis (SDSE) in Swiss albino mice - Sagar Patel; Monalisa Sahoo; Jigarji Chaturji Thakor; Rajendra Singh; Karampal Singh; Salauddin Qureshi; Shailesh Kumar Patel; Varsha Jayakumar; Akash Balasaheb Mote; Susen Kumar Panda; Aditya Prasad Acharya; Ritun Patra; et al. (Brazilian Journal of Microbiology, 2026)

Climatic and biotic determinants of Dalbergia latifolia survival and adaptability beyond its native range: GLMM model evaluation and validation - Tushal Srivastava; Pankaj Kumar; Lekhendra Sahu; Rama Kant; Rajendra K. Meena; Shailesh Pandey; Maneesh S. Bhandari (Trees, 2026)

Integrated Transcriptomic and Small RNA Profiling Reveals Regulatory Networks Associated With Seed Protein Accumulation in Chickpea (Cicer arietinum L.) - Gopal Kalwan; Deshika Kohli; Yashwant Kumar Yadava; Sheel Yadav; Suruchi Khanna; Ila Joshi; MS Nimmy; S. V. Amitha Mithra; Biswajit Mondal; Shailesh Tripathi; Satvir Kaur Grewal; Kishor Gaikwad; et al. (Journal of Plant Growth Regulation, 2026)

Physiological responses to nitrite toxicity in freshwater pearl mussel (Lamellidens marginalis) - Victoria Tripathy; E M Chhandaprajnadarsini; Pankaj Kumar Tiwari; Pushpa Choudhary; Yashaswi Nayak; Shailesh Saurabh (Ecotoxicology, 2026)

Abiotic Stress-Mediated Modulation of the tncRNome: Unraveling tRNA-Derived RNA Networks in Plant Adaptive Responses - Shafaque Zahra; Rashmi Gangwar; Sneha Tiwari; Dipul Kumar Biswas; Amarjeet Singh; Shailesh Kumar (Journal of Plant Growth Regulation, 2026)

Age and sex dependent shift in murine gut microbiome reveals pathological links to host cardiovascular and metabolic pathways - Meena Kumari Palani Kumar; Krishna S. Iyer; Shailesh K. Shahi; Juan Antonio Raygoza Garay; Ashutosh Mangalam; Sanjana Dayal (GeroScience, 2026)
The gut microbiome undergoes dynamic, sex-dependent changes across the lifespan. However, comprehensive studies examining the combined effects of age and sex are limited. This study investigated both compositional and functional alterations in the gut microbiome of young (4 months, n = 14) and aged (20 months, n = 20) C57BL/6 J mice of both sexes using 16S rRNA gene (V3–V5) sequencing. Microbial community structure and predicted functional profiles were analyzed via QIIME2 and PICRUSt2, with pathway annotation based on MetaCyc. Compared to aged mice, young mice exhibited higher alpha diversity, with the highest increase observed in young females. This sex-specific difference was lost in aged mice. Aging was also associated with an increased Firmicutes-to-Bacteroidetes ratio, and distinct shifts in key taxa, including increased Lactobacillus and Roseburia and reduced Bacteroides and Lachnospiraceae. Functional prediction revealed substantial age-related metabolic shifts, especially in females showing alteration in 45 pathways including upregulation of branched-chain amino acid (BCAA) metabolism, uric acid metabolism, and lipopolysaccharide biosynthesis. To directly link alterations in microbial BCAA metabolism with host metabolic outcomes, fecal abundance of the bacterial BCAA aminotransferase gene (ilvE) was quantified and found to be significantly increased in aged mice. Concurrently, aged mice exhibited higher plasma levels of BCAA, insulin, and random glucose, indicating age-associated metabolic dysregulation. Fecal ilvE abundance associated positively with plasma BCAA levels, and negatively with blood glucose in aged mice, suggesting a link between microbial BCAA metabolism and host glucose homeostasis. Our findings demonstrate that gut microbiome composition and function are influenced by both age and sex. We also showed that these alterations in microbial BCAA metabolism are associated with host metabolic parameters during aging. Our findings underscore the importance of incorporating both age and sex as biological variables in microbiome research and may inform development of age- and sex-specific microbiome-targeted interventions.

Trade-offs and synergies of conservation agriculture practices in the maize–wheat system: Improving yield, profitability, and soil resilience in a changing climate - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; R.K. Singh; Kapila Shekhawat; B.S. Dwivedi; P.K. Upadhyay; Sunita Kumari Meena; Amit Kumar; Adarsh Kumar; Gaurav Verma; et al. (Field Crops Research, 2026)

Leveraging Butylated hydroxyanisole to enhance cell Biovolume, photosynthetic performance and lipid productivity without compromising biodiesel quality of Chlorella sp. - Simran Maratha; Sana Parveen; Ruchika Agarwal; Shailesh Kumar Patidar (Bioresource Technology, 2026)

Characterization of Genetic Diversity in Amaranthus Species Using Morpho-Molecular Markers - Ajay Kumar Sharma; Vidya Sagar; S. V. Dwivedi; Jyoti Devi; Neetu; Shailesh K. Tiwari; Sunil K. Singh; N. Rai; Rajesh Kumar; T. K. Behera (Indian Journal of Genetics and Plant Breeding, 2026)

Environmental geochemistry and quality assessment of springs water in the Sikkim Himalaya: an entropy-weighted & machine learning approach - Shailesh Kumar Yadav; Anil Kumar Misra; Nishchal Wanjari; Rakesh Kumar Ranjan; Shive Prakash Rai; Raju Rai (Environmental Geochemistry and Health, 2026)

Radio-frequency vacuum drying of Mangifera indica wood: insights into drying kinetics, microstructural changes and physico-mechanical properties - Kamal Mishra; Rohit Sharma; Anil Kumar Sethy; Manoj Kumar Dubey; Satyen Das; Shailesh Namdev Patil; Dharmesh Verma (Journal of the Indian Academy of Wood Science, 2026)

Coupled role of Westerlies and Indian Summer Monsoon in the climatic variability of Kashmir Valley, NW India during the Late Quaternary - Shirish Verma; Binita Phartiyal; Shailesh Agrawal; P. Morthekai; M.C. Manoj; Rakesh Chandra; Lakhi Narayan Sahu; Sumit Sagwal; Pankaj Kumar; Abhayanand Singh Maurya (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

GC-MS metabolite profiling and computational ranking of Butea monosperma and their predicted contribution to antimicrobial activity against MRSA - Pramod Kumar Mahish; Shweta Singh; Kaushal Kumar Sahu; Dakeshwar Kumar Verma; Gajanan Ghodake; Ravishankar Chauhan; Shushil Kumar Rai; Shailesh Kumar Jadhav (Phytochemistry Letters, 2026)

Climate-resilient agriculture strategies to address the challenges of agri-food security and climate change - Raj Kumar Jat; Vijay Singh Meena; RK Sohane; RK Jha; Abhay Kumar; Ujjwal Kumar; Anjani Kumar; RN Singh; Shubham Durgude; Suneel Kumar; Illathur R. Reddy; S. Pazhanisamy; et al. (Field Crops Research, 2026)

Hydrodynamic Fate and High-Hazard Source Apportionment of Microplastics in Freshwater Bodies of Semi-Arid Rajasthan, India - Charulata Sivodia; Mohd Ashraf Dar; Milap Dashora; Ommer Ahad Bhat; Shailesh Kumar Patidar; Garima Kaushik (Water Conservation Science and Engineering, 2026)

Effects of Specimen Geometry and Bamboo Biochar Amendment on Anisotropic Shrinkage Behavior of Soils - Shailesh Kumar Yadav; Ramakrishna Bag (Geotechnical and Geological Engineering, 2026)

Correlation of enhanced antioxidant enzyme activity and phenolic content with downy mildew resistance in cucumber (Cucumis sativus L.) - Rahul Kumar; Vidya Sagar; Dharm Pal Singh; Pragya; Sudhakar Pandey; Rajeev Kumar; Jyoti Devi; Nakul Gupta; Shailesh Kumar Tiwari; Nagendra Rai; Rajesh Kumar (Journal of Plant Pathology, 2026)

Enhancing productivity, profitability, and sustainability of wheat production through conservation agriculture strategies - Ravindra K. Tiwari; Bharati Upadhaya; MS Kundu; Anupma Kumari; Raj Kumar Jat; Vinita Kashyap; Kaushal Kishor; Sanjay Kumar; Shailesh Kumar; Vijay Singh Meena (Environment, Development and Sustainability, 2026)

Genome-wide association analysis using multi model approach identified novel associations for plant architectural traits in chickpea germplasm collection - Rahul Raiya; Hemant Kumar Yadav; Kuldeep Kumar; Nitish Ranjan Prakash; Swarup Kumar Parida; Chellapilla Bharadwaj; Venkatraman Hegde; Shailesh Tripathi (The Nucleus, 2026)

Improved osmotic vis-à-vis ionic stress tolerance component traits and associated gene expression bestow salinity tolerance to chickpea at the flowering stage - R. Suriyaprakash; Lekshmy Sathee; Shailesh Tripathi; Aman Singh; Viswanathan Chinnusamy; Arun Kumar (Journal of Plant Biochemistry and Biotechnology, 2026)

Genome survey sequencing-based SSR marker development and population genetic structure of Dalbergia sissoo: a premier hardwood timber species - Rajendra K. Meena; Payal Dhyani; Priyanka Kashyap; Ajay Sojitra; Maneesh S. Bhandari; Shailesh Pandey; Rama Kant; Ajay Thakur; Ashok Kumar; Santan Barthwal (The Nucleus, 2026)

Combating land degradation and desertification through forest-based technological interventions - Maneesh S. Bhandari; Anamika Jhangra; Parmanand Kumar; Lokinder Sharma; Rajendra K. Meena; Shailesh Pandey; Vinay Kumar Yadav; Santan Barthwal (Environmental Sustainability, 2026)

Performance evaluation of a zwitterionic surfactant for the emulsification of an Indian heavy crude oil for pipeline transportation - Rajiv Choudhary; Shailendra Singh; Shailesh Kumar; Sidharth Gautam; Amit Kumar (Fuel, 2026)

Microplastic exposure and its impact on the growth and physiological functions of Cicer arietinum - Garima Kaushik; P. Manuraj; Mohd Ashraf Dar; Preksha Palsania; Shalni Satya; Ommer Ahad Bhat; Shailesh Kumar Patidar (Biocatalysis and Agricultural Biotechnology, 2026)

A seasonal study of uranium in groundwater of Dhaulpur district of Rajasthan, India - Kalpana Gupta; Rashmy Nair; Kalawati Saini; Ashok Kumar Gupta; Sunil Kumar Sahoo; Shailesh Nath Tiwari; Tejpal Menaria (Sustainable Water Resources Management, 2026)

Integration of medical genetics and genomics into faculty development programs in india: assessment of success and experience of genetic research centre - Shaini Joseph; Neha Minde; Shiny Babu; Harshvardhan Gawde; Chinna Naik; Venkanna Bhanothu; DVS Sudhakar; Juili Bharankar; Tanvi Agarbattiwala; Amisha Kumar; Geetanjali Sachdeva; Smita D. Mahale; et al. (Journal of Community Genetics, 2026)

The key drivers of streamflow recession variability and their implications for robust parameterization of recession processes - Man Gao; Zhe Wang; Xi Chen; Jianzhi Dong; Shailesh Kumar Singh (Hydrological Sciences Journal, 2026)

Quantifying Predictability and Information Transfer in Rainfall-Runoff Process - Chongli Di; Shailesh Kumar Singh; Jianzhi Dong; Jianzhu Li; Jun He (Water Resources Management, 2026)

Development of Lysigenous Aerenchyma in Root Alleviates the Waterlogging Stress in Little Millet - Ritik Raj; Shailesh Kumar; Sweta Mishra; Dayanji Sherpa (Tropical Plant Biology, 2025)

Development of plant tissue culture system for Nyctanthes arbor-tristis L. in a controlled environmental system from shoot-tip culture and genetic homogeneity evaluation utilizing inter simple sequence repeat (ISSR) and start codon targeted (SCoT) markers - Awadhesh Kumar Mishra; Kavindra Nath Tiwari; Pallavi Mishra; Rajesh Saini; Shailesh Kumar Tiwari; Sunil Kumar Mishra (Genetic Resources and Crop Evolution, 2025)

Comprehensive study of tRNA-derived fragments in plants for biotic stress responses - Supriya P. Swain; Niyati Bisht; Shailesh Kumar (Functional & Integrative Genomics, 2025)

Plant phenotypic adjustments in response to changes in atmospheric pCO 2 : insights from δ 13 C values and stomatal index in C 3 plant leaves - Mohan Kumar; Shailesh Agrawal; Vijayananda Sarangi; Anjum Farooqui; Priyanka Singh; Sheikh Nawaz Ali; P. Morthekai; Deepika Tripathi; Anurag Kumar; Salman Khan; Anupam Sharma; Dhruv Sen Singh (Isotopes in Environmental and Health Studies, 2025)

A comprehensive review on poisonous mushrooms: The revolutionary potential of mycotoxins in medicine and beyond - Khemraj Sahu; Sajal Saju Deo; Shailesh Kumar Jadhav; Nagendra Kumar Chandrawanshi (Toxicon, 2025)

Exploring groundwater quality and subsurface characteristics using Vertical Electrical Sounding (VES) in the Basantar watershed of J&K India - Ajay Kumar Taloor; Shailesh Bhatnagar; Savita; Ravi Sharma (Journal of Geochemical Exploration, 2025)

Assessing post-emergence herbicides in chickpea (Cicer arietinum L.) for economic benefits, yield response, and weed control under different mega-environments in India - Narendra Kumar; C.P. Nath; K.K. Hazra; Shailesh Tripathi; G.P. Dixit; Kamal Tiwari; Guriqbal Singh; Harpreet Kaur Virk; K.C. Gupta; Dasharath Prasad; Brij Nandan; Sunil Kumar; et al. (Field Crops Research, 2025)

Strain improvement of Cordyceps militaris for optimized bioactive metabolite biosynthesis: current progress and prospective approaches - Varsha Meshram; Shailesh Kumar Jadhav; Nagendra Kumar Chandrawanshi (Antonie van Leeuwenhoek, 2025)

Seaweed extract: a potential modulator of productivity and bulb quality in onion (Allium cepa L.) - S Thirumalesh; Shailesh Kumar Singh; Priyanka Upadhyay; Manish Bakshi (The Nucleus, 2025)

Performance Assessment of a Manually Operated Jaggery Cube Molding Machine - Dilip Kumar; Shailesh Kumar Markam; D. Khokhar; Priyanka Singh (Sugar Tech, 2025)

Micropropagation of Drypetes roxburghii (Wall.) Hurusawa—a valuable medicinal plant through root culture and evaluation of its genetic fidelity and metabolomics - Rajesh Saini; Awadhesh Kumar Mishra; Pallavi Mishra; Praveen Kumar Shukla; Jyoti Vishwakarma; Kavindra Nath Tiwari; Shailesh Kumar Tiwari; Jasmeet Singh (In Vitro Cellular & Developmental Biology - Plant, 2025)

Evaluation of Agromorphological and Yield Traits in Strawberry (Fragaria X ananassa Duch.) Genotypes Under Hydroponic Cultivation - Pallvi Verma; Shailesh Kumar Singh; Priyanka Upadhyay; Sanjay Singh; Manish Bakshi (Applied Fruit Science, 2025)

Nanoagrochemicals: Ensuring sustainable productivity through nutrient and pest management in strawberry (Fragaria × ananassa Duch.) - Lakhwinder Singh; Ramesh Kumar Sadawarti; Diksha Thakur; Shailesh Kumar Singh; Anis Ahmad Mirza (Biocatalysis and Agricultural Biotechnology, 2025)

Unlocking the Economic Potential of Potato Cultivars for Mini-tuber Production Under Aeroponic Culture - Paramjit Singh; Priyanka Upadhyay; Shailesh Kumar Singh (Potato Research, 2025)

Calcium Dynamics in Strawberry (Fragaria x ananassa Duch.) Plant: from Soil to Fruit - Sudhanshu Singh; Akash Kumar; Niharika Thakur; Avantika Bisht; Anmol; Shailesh Kumar Singh; Manish Bakshi (Journal of Soil Science and Plant Nutrition, 2025)

Late Quaternary productivity and hydrographic variability in the upper water column of the Agulhas Return Current region as inferred from planktic foraminifera - Divya Verma; Pawan Govil; Shailesh Agrawal; P. Morthekai; Brijesh Kumar; Hidayatullah Khan (Quaternary International, 2025)

Pangenome-wide identification, evolutionary analysis, and characterization of WOX gene family among Brassica Triangle of U's genomes - Prabhakaran Soundararajan; AT Vivek; Gokul Babu Suresh; Bhavya Shukla; Kanchan B.M. Singh; Shailesh Kumar; Abinaya Manivannan (Plant Gene, 2025)

Suitable Planting Material with Integrated Nutrient Management Can Enhance Productivity, Nutrient Use Efficiency and Profitability of Sugarcane - Sumit Sow; Navnit Kumar; Lalita Rana; A. K. Singh; Vipin Kumar; Harendra Singh; Kavita; Shailesh Kumar (Journal of Soil Science and Plant Nutrition, 2025)

Development of breeding lines with multiple stress tolerance to cold, drought, and high-temperature stress in rice (Oryza sativa L.) - Rahul Priyadarshi; Shailesh Yadav; Mamatha Pettem; Challa Venkateshwarlu; K. J. Pranesh; Vikas K. Singh; Arvind Kumar (Euphytica, 2025)

Advances in salinity tolerance breeding in tomato: from conventional breeding tools to genome editing - Mohd Aamir; Sarvesh P. Kashyap; Ram Krishna; Pallavi Mishra; Pooja Singh; Waquar Akhter Ansari; Durga Prasad Moharana; Shailesh Kumar Tiwari; Prabhakar Mohan Singh; N. Rai; Achuit Kumar Singh (Environmental Sustainability, 2025)

A Geoinformatics-Based Comparative Study of Multi-Criteria Decision Making Approaches of Groundwater Potential Zoning in Ken Basin, India - Deepak Patle; Manoj Kumar Awasthi; Shailesh Kumar Sharma; Yogesh Kishore Tiwari (Journal of the Indian Society of Remote Sensing, 2025)

Decontamination of Sewage Wastewater by an Aeration Method Utilizing Water Hardness-Reducing Spirulina platensis - Jyoti Narsude; Jayesh Jadhav; Vikas Rena; Aarif Khan; Ratna Chauhan; Rushikesh Sonawane; Sanjay Dhole; Vikram Pandit; Akash Jadhav; Manik Awale; Shailesh Kumar Patidar; Bhagawan Dheravath; et al. (Current Microbiology, 2025)

Fusion transcripts in plants: hidden layer of transcriptome complexity - Simran Arora; Fiza Hamid; Shailesh Kumar (Trends in Plant Science, 2025)

Modulating Productivity of Strawberries (Fragaria x ananassa Duch.) Through Artificial Full-Spectrum Light in Indoor Vertical Farming - Pallvi Verma; Gurpreet Singh; Shailesh Kumar Singh; Anis Ahmad Mirza; Manish Bakshi; Anmol; Lakshya; Lokesh Kumar; Rupesh (Journal of Soil Science and Plant Nutrition, 2025)

Efficacy of Plant Growth Regulators for the Modulation in the Productivity of Strawberries (Fragaria x ananassa Duchesne) - Lakhwinder Singh; Ramesh Kumar Sadawarti; Shailesh Kumar Singh; Shaifali; Anis Ahmad Mirza (Journal of Plant Growth Regulation, 2025)

Assessing the predicted impact of single amino acid substitutions in MAPK proteins for CAGI6 challenges - Paola Turina; Maria Petrosino; Carlos A. Enriquez Sandoval; Leonore Novak; Alessandra Pasquo; Emil Alexov; Muttaqi Ahmad Alladin; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Jianlin Cheng; et al. (Human Genetics, 2025)

Assessing the predicted impact of single amino acid substitutions in calmodulin for CAGI6 challenges - Paola Turina; Giuditta Dal Cortivo; Carlos A. Enriquez Sandoval; Emil Alexov; David B. Ascher; Giulia Babbi; Constantina Bakolitsa; Rita Casadio; Piero Fariselli; Lukas Folkman; Akash Kamandula; Panagiotis Katsonis; et al. (Human Genetics, 2025)

Metabolic interactions between microalgae and bacteria: Multifunctional ecological interplay and environmental applications - Shailesh Kumar Patidar (Algal Research, 2025)

Western equatorial Indian Ocean surface hydrographic variations inferred from isotopic record of planktic foraminifera Globigerinoides ruber during last ~412,000 years - Brijesh Kumar; Pawan Govil; Shailesh Agrawal; Pankaj Kumar; Divya Verma; Hidayatullah Khan (Journal of Earth System Science, 2025)

Exploring the multi-faceted health risks of heavy metals exposure in Sikkim’s unique Himalayan ecosystem, India - Shailesh Kumar Yadav; Bidyutjyoti Baruah; Kuldeep Dutta; Krity Rai; Anirud Rai; Rajeev Rajak; Aparna Gupta; Anil Kumar Misra; Nishchal Wanjari; Rakesh Kumar Ranjan (Environmental Monitoring and Assessment, 2025)

Geochemical fractionation and bioavailability of heavy metals in the middle gangetic plain: Assessing ecological risks in water and sediment systems - Shailesh Kumar Yadav; AL. Ramanathan (Science of The Total Environment, 2025)

Evolving marine sedimentation, redox stratification, and biogeochemical cycling in mid- to low-latitudinal non-frozen waters during late Neoproterozoic global-scale climatic transitions - Arunava Sen; Soumik Mukhopadhyay; Eva E. Stüeken; Pradip Samanta; Subir Sarkar; Soumyadeep Bose; Shailesh Agarwal; Anurag Kumar (Precambrian Research, 2025)

High-resolution Indian summer monsoon (ISM) records during the last 1400 yrs BP from the Mahi river basin, Mainland Gujarat, India - Kamlesh Kumar; Anupam Sharma; Shailesh Agrawal (Journal of Sedimentary Environments, 2025)

Microplastic pollution: A global perspective in surface waters, microbial degradation, and corresponding mechanism - Mohd Ashraf Dar; Preksha Palsania; Shalni Satya; Milap Dashora; Ommer Ahad Bhat; Sana Parveen; Shailesh Kumar Patidar; Garima Kaushik (Marine Pollution Bulletin, 2025)

Impact of catchment and climate attributes on flood generating processes and their effect on flood statistics - Svenja Fischer; Markus Pahlow; Shailesh Kumar Singh (Journal of Hydrology, 2025)

Identification of suitable sites for different artificial groundwater recharge structures for sustainable water resources management in Ken River Basin - Deepak Patle; Sourabh Nema; Manoj Kumar Awasthi; Shailesh Kumar Sharma (Environment, Development and Sustainability, 2024)

Euwallacea perbrevis (Schedl, 1951) and associated novel fungal symbiont, Fusarium sp.: A potential cause of wilting in cocoa, Theobroma cacao in India - Shivaji Hausrao Thube; R Thava Prakasa Pandian; M. Rajkumar; Merin Babu; A. Josephrajkumar; Santhoshkumar P; B.J. Nirmal Kumar; Vinayaka Hegde; Balanagouda Patil; H. Rajashekara; T. Prabhulinga; Babasaheb B. Fand; et al. (Crop Protection, 2024)

Characterization of biotic and abiotic signatures of modern lake sediments of western India, and its palaeo-environmental implications - Anjali Trivedi; Sheikh Nawaz Ali; M.C. Manoj; Shailesh Agrawal; Anupam Sharma; Binita Phartiyal; Kamlesh Kumar; Arvind Tiwari; P. Morthekai; Biswajeet Thakur; Anjum Farooqui; Mohd Ikram; et al. (Quaternary International, 2024)

Efficacy of nano-minerals for productivity and economics of capsicum under naturally ventilated polyhouse - Shraddha Mahajan; Shweta; Himanshi Dwivedi; Shailesh Kumar Singh (Vegetos, 2024)

A new insight for geophysical and geospatial mapping quaternary alluvium of Indo-Gangetic plains for exploration and assessment of groundwater in Haryana, India - Dewashish Kumar; Savita; Shailesh Bhatnagar; Amal Joy (Groundwater for Sustainable Development, 2024)

Distribution, toxicity load and risk assessment of heavy metals in the groundwater of Dhemaji, Assam, India - Shailesh Kumar Yadav; Binud Attry; Sudeep Shukla; Shruti Dutta; Khushboo Sharma; Rajeev Rajak; Aparna Gupta; Bidyutjyoti Baruah; Rakesh Kumar Ranjan (Chemosphere, 2024)

Assessment of Heavy Metal and E. coli Contamination in Water Sources of the East and South Districts, Sikkim Himalaya, India - Krity Rai; Anil Kumar Misra; Rakesh Kumar Ranjan; Nishchal Wanjari; Rajeev Rajak; Shailesh Kumar Yadav; Richard Rai; Md. Abdullah Khan (Water Conservation Science and Engineering, 2024)

Non-traumatic myelopathy as a rare cause of acute-onset longitudinally extensive transverse myelitis - Pooja Anand; Rajesh Kumar Singh; Deepti Vibha; Shailesh Gaikwad; Manjari Tripathi (Acta Neurologica Belgica, 2024)

Evaluation of the effects of dust pollution on specific plant species near and around the marble mining site in Rajasthan, India - Naziya Tarannum; Natasha Rathore; Ashok Natwadiya; Shailesh Kumar; Nivedita Chaudhary (Environmental Science and Pollution Research, 2024)

Transcriptome analysis of mantle and pearl sac of freshwater pearl mussel Lamellidens marginalis to identify biomineralisation-associated genes - Sonal Suman; A. Pavan-Kumar; Shailesh Saurabh; Vinaya Kumar Katneni; Sudheesh K. Prabhudas; Shubham Varshney; Sweta Pradhan; P. Gireesh-Babu; Rekha Das; Aparna Chaudhari (Molluscan Research, 2024)

Abrupt intensification of AMOC and monsoonal winds during mid-MIS4 (Heinrich Event 6) in the western Arabian Sea - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Shailesh Agrawal; Pankaj Kumar; Brijesh Kumar; Divya Verma (Global and Planetary Change, 2024)

Tiny but mighty: metal nanoparticles as effective antimicrobial agents for plant pathogen control - Abhijeet Shankar Kashyap; Nazia Manzar; Shailesh Kumar Vishwakarma; Chetna Mahajan; Utpal Dey (World Journal of Microbiology and Biotechnology, 2024)

Physicochemical assessment of industrial effluents of Kala Sanghian drain, Punjab, India - Anju Mangotra; Shailesh Kumar Singh (Environmental Monitoring and Assessment, 2024)

Deformities in fish: A barrier for responsible aquaculture and sustainable fisheries - Gyan Chandra; V. P. Saini; Shailesh Kumar; Dorota Fopp‐Bayat (Reviews in Aquaculture, 2024)
Fish deformities are detrimental to aquaculture and conservation initiatives; it is also an ethical problem and causes substantial financial losses to the aquaculture industry. The exact mechanism of deformities is still a mystery. Several factors cause deformities in fish; it seems that the deformations are inevitable but can be minimised by adopting good aquaculture practices such as proper broodstock husbandry, standard breeding and larval rearing protocol, management of water quality parameters, and providing nutritionally balanced feed, especially to the broodstock and developing larvae. In addition, it can be minimised by early detection of deformities, especially at the embryonic and larval stages. Monitoring of stocking materials should be an essential part of responsible aquaculture and conservation programmes; stocking materials should be free from any types of deformities as it affects not only aquaculture production, profitability and success of conservation programmes but also the reoccurrence of deformities in nature. The mechanism behind deformities and the development of low‐cost, robust methods/tools for detecting deformities in fish remain a challenge. Still, the opportunity exists to develop a robust marker that can predict deformities even at early embryonic and larval stages.

Bicarbonate-assisted microalgae cultivation for drinking water RO reject recycling and bioproduct generation - Mamta Bhandari; Shailesh Kharkwal; Sanjeev Kumar Prajapati (Bioresource Technology Reports, 2024)

Modulation of terpenoid indole alkaloid pathway via elicitation with phytosynthesized silver nanoparticles for the enhancement of ajmalicine, a pharmaceutically important alkaloid - Sachin Kumar Verma; Danswrang Goyary; Amit Kumar Singh; Sivalingam Anandhan; Soom Nath Raina; Sadanand Pandey; Shailesh Kumar; Neeraj Khare (Planta, 2024)

Differential gene expression analysis reveals the fast-growth mechanisms in Melia dubia at different stand ages - K Rajarajan; Shailesh Verma; Sakshi Sahu; A Radhakrishna; Naresh Kumar; E Priyadarshini; AK Handa; A Arunachalam (Molecular Biology Reports, 2023)

Population structure and genetic differentiation analyses reveal high level of diversity and allelic richness in crop wild relatives of AA genome species of rice (Oryza sativa L.) in India - Aswin Mahendran; Mahesh C. Yadav; Shailesh Tiwari; Rakesh Kumar Bairwa; S. Gopala Krishnan; Mukesh Kumar Rana; Rakesh Singh; Tapan Kumar Mondal (Journal of Applied Genetics, 2023)

A probabilistic framework for robust master recession curve parameterization - Man Gao; Xi Chen; Shailesh Kumar Singh; Jianzhi Dong; Lingna Wei (Journal of Hydrology, 2023)

Theoretical derivation of hydraulic geometry equations for a gravel bed river channel - George A. Griffiths; Shailesh Kumar Singh (Advances in Water Resources, 2023)

Bacterial quorum sensing precursors N-(3-Oxododecanoyl)-L-homoserine lactone & N-(3-Hydroxyoctanoyl)-DL-homoserine lactone ameliorate algal biomass, lipids and fatty acids - Sana Parveen; Shailesh Kumar Patidar (Chemical Engineering Journal, 2023)

Evaluation of uranium content and annual ingestion dose in the surface and ground water bodies of Chittorgarh, Rajasthan, India - Tejpal Menaria; Shailesh Nath Tiwari; Akshay Kumar Patra; Inampudi Vijaya Saradhi; A Vinod Kumar; Rama Kanwar Khangarot; Devendra Singh Rathore (Environmental Monitoring and Assessment, 2023)

Development of a new agro-meteorological drought index (SPAEI-Agro) in a data-scarce region - Pallavi Kumari; Shaik Rehana; Shailesh Kumar Singh; M. Inayathulla (Hydrological Sciences Journal, 2023)

Surface and thermocline ocean circulation intensity changes in the western Arabian Sea during ∼172 kyr - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Shailesh Agrawal; Pankaj Kumar; Brijesh Kumar; Divya Verma (Quaternary Science Reviews, 2023)

Ecological niche modelling and population genetic analysis of Indian temperate bamboo Drepanostachyum falcatum in the western Himalayas - Rajendra K. Meena; Nitika Negi; Rajeev Shankhwar; Maneesh S. Bhandari; Rama Kant; Shailesh Pandey; Narinder Kumar; Rajesh Sharma; Harish S. Ginwal (Journal of Plant Research, 2023)

Westerly-monsoon variations since the last deglaciation from semi-arid Ladakh region, Trans Himalaya, India - Debarati Nag; Binita Phartiyal; Shailesh Agrawal; Pankaj Kumar; Rajveer Sharma; Kamlesh Kumar; Anupam Sharma; Mallickarjun Joshi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Projection of net primary production under changing environment in Xinjiang using an improved wCASA model - Shu Song; Jun Niu; Shailesh Kumar Singh; Taisheng Du (Journal of Hydrology, 2023)

Modern biotic and abiotic analogues from the surface soil of Ganga-Ghaghara-Gandak interfluves of the Central Ganga Plain (CGP), India: Implications for the palaeoecological reconstructions - Swati Tripathi; Biswajeet Thakur; Anupam Sharma; Binita Phartiyal; Sadhan Kumar Basumatary; Ruby Ghosh; Kamlesh Kumar; M.C. Manoj; Shailesh Agrawal; Anjum Farooqui; Pooja Tiwari; Korobi Saikia; et al. (CATENA, 2023)

Reconstruction of landscape and climate of the largest drainage basin in the Ladakh Range, NW Trans Himalaya during the last 7000 years - Priyanka Joshi; Binita Phartiyal; Mallickarjun Joshi; Shailesh Agrawal; Pankaj Kumar; Rajveer Sharma (CATENA, 2023)

Recycling drinking water RO reject for microalgae-mediated resource recovery - Mamta Bhandari; Shailesh Kharkwal; Sanjeev Kumar Prajapati (Resources, Conservation and Recycling, 2023)

Last 10 millennial history of Indian summer monsoon in the Bengal region – a multi-proxy reconstruction from a lacustrine archive - Ruby Ghosh; Korobi Saikia; Oindrila Biswas; Shailesh Agrawal; P. Morthekai; Mohammad Arif; Binita Phartiyal; Anupam Sharma; Neha Singh; Dipak Kumar Paruya; Pyarimohan Maharana; Mayank Shekhar; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Environmental Flows Allocation for a Tropical Reservoir System by Integration of Water Quantity (SWAT) and Quality (GEFC, QUAL2K) Models - Mummidivarapu Satish Kumar; P. N. Chandi Priya; Rehana Shaik; Shailesh Kumar Singh (Water Resources Management, 2023)

Impact of single and dual deficiency of nitrogen and iron on photosynthesis and fluorescence parameters in hydroponically and field grown bread wheat - Dalveer Singh; Afroz Alam; Shailendra K. Jha; Sudhir Kumar; Rakesh Pandey; Viswanathan Chinnusamy; Shailesh Tripathi; Lekshmy Sathee (Plant Physiology Reports, 2022)

Genome-wide identification, characterization, and expression profiling of 14-3-3 genes in legumes - Srija Chakraborty; Prabhakaran Soudararajan; Shailesh Kumar (Plant Biotechnology Reports, 2022)

Groundwater vulnerability assessment using DRASTIC model in Niwari District of Bundelkhand Region, Madhya Pradesh, India - Deepak Patle; Sourabh Nema; Manoj Kumar Awasthi; Shailesh Kumar Sharma; Yogesh Kishore Tiwari (Arabian Journal of Geosciences, 2022)

BURP domain-containing genes in legumes: genome-wide identification, structure, and expression analysis under stresses and development - Pragya Chitkara; Nikita Poddar; Amarjeet Singh; Shailesh Kumar (Plant Biotechnology Reports, 2022)

Seroprevalence of SARS-CoV-2 infection among frontline police personnel in Mumbai, India - Shibal Bhartiya; Babasaheb V Tandale; Shailesh D Pawar; Nishant Kumar (VirusDisease, 2022)

Surface hydrographic variations in the western Arabian Sea through the last 172 kyr - Hidayatullah Khan; Pawan Govil; Rajani Panchang; Pankaj Kumar; Shailesh Agrawal (Geo-Marine Letters, 2022)

Germplasm conservation of economically important medicinal plant Nyctanthes arbor-tristis L. through encapsulation technique and maintenance under slow growth condition - Awadhesh Kumar Mishra; Kavindra Nath Tiwari; Pallavi Mishra; Sunil Kumar Mishra; Shailesh Kumar Tiwari (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Detection of porcine enteric picornaviruses from faecal samples of Indian pigs - Shailesh Kumar Patel; Aditya Agrawal; Mamta Pathak; Alok Singh; Rajat Varshney; Jigyasa Rana; G. Saikumar (VirusDisease, 2022)

Exploration of antigenic determinants in spike glycoprotein of SARS-CoV2 and identification of five salient potential epitopes - Aditya Agrawal; Rajat Varshney; Mamta Pathak; Shailesh Kumar Patel; Vishal Rai; Sourabh Sulabh; Rohini Gupta; Khushal Singh Solanki; Ritu Varshney; Ramadevi Nimmanapalli (VirusDisease, 2021)

Synthesis and Characterization of Chitosan-Alginate-Based Cross-linked Copolymer for the Effective Removal of Methylene Blue from Its Aqueous Solution - Sumit Kumar; Shailesh Kumar; Ashok Kumar; Swati Rastogi; Deepak Kumar (Water, Air, & Soil Pollution, 2021)

Organogenesis from Leaf Tissue of Spondias pinnata (L. f.) Kurz, SEM study and Genetic Fidelity Assessment by ISSR and ScoT - Pooja Jaiswal; Nishi Kumari; Sarvesh Pratap Kashyap; Shailesh Kumar Tiwari (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

The role of disinfectants and sanitizers during COVID-19 pandemic: advantages and deleterious effects on humans and the environment - Kuldeep Dhama; Shailesh Kumar Patel; Rakesh Kumar; Rupali Masand; Jigyasa Rana; Mohd. Iqbal Yatoo; Ruchi Tiwari; Khan Sharun; Ranjan K. Mohapatra; Senthilkumar Natesan; Manish Dhawan; Tauseef Ahmad; et al. (Environmental Science and Pollution Research, 2021)

Genetics of lodging resistance in chickpea (Cicer arietinum L) - Rahul Raiya; Venkatraman Hegde; Veda Krishnan; Chellapilla Bharadwaj; Shailesh Tripathi; Pradeep Kumar Jain (Euphytica, 2021)

Molecular strategies to enhance stability and catalysis of extremophile-derived α-amylase using computational biology - Nisha Gupta; Esmil Beliya; Jai Shankar Paul; Shubhra Tiwari; Shriram Kunjam; Shailesh Kumar Jadhav (Extremophiles, 2021)

From Guest Editors’ Desk - Shailesh R. Nayak; A. Senthil Kumar (Journal of the Indian Society of Remote Sensing, 2021)

Remembering IRS-1C Mission: The “Game Changer” of Indian Earth Observation Program - A. Senthil Kumar; N. Aparna; Shailesh R. Nayak (Journal of the Indian Society of Remote Sensing, 2021)

The Feasibility of Multi-Criteria Decision Making Approach for Prioritization of Sensitive Area at Risk of Water Erosion - Sarita Gajbhiye Meshram; Vijay P. Singh; Ercan Kahya; Ehsan Alvandi; Chandrashekhar Meshram; Shailesh Kumar Sharma (Water Resources Management, 2020)

Lung cancer identification: a review on detection and classification - Shailesh Kumar Thakur; Dhirendra Pratap Singh; Jaytrilok Choudhary (Cancer and Metastasis Reviews, 2020)

Palaeoredox link with the late Neoproterozoic–early Cambrian Bilara carbonate deposition, Marwar Supergroup, India - A. H. Ansari; S. K. Pandey; Kamlesh Kumar; Shailesh Agrawal; Shamim Ahmad; Mayank Shekhar (Carbonates and Evaporites, 2020)

Factors affecting the efficiency of in vitro regeneration from seedling-derived nodal explants of Nyctanthes arbor-tristis L. and evaluation of genetic fidelity - Awadhesh Kumar Mishra; Kavindra Nath Tiwari; Pallavi Mishra; Shailesh Kumar Tiwari; Sunil Kumar Mishra; Jasmeet Singh (Plant Biosystems, 2020)

Effect of exogenous additives on oxidative stress and defense system of a tree: Zanthoxylum armatum DC. under in vitro conditions - Gyanmani Ekka; Shailesh Kumar Jadhav; Afaque Quraishi (Plant Cell, Tissue and Organ Culture (PCTOC), 2020)

HvWRKY23 regulates flavonoid glycoside and hydroxycinnamic acid amide biosynthetic genes in barley to combat Fusarium head blight - Shailesh Karre; Arun Kumar; Kalenahalli Yogendra; Udaykumar Kage; Ajjamada Kushalappa; Jean-Benoit Charron (Plant Molecular Biology, 2019)

Lesson Learnt from Recall of Valsartan and Other Angiotensin II Receptor Blocker Drugs Containing NDMA and NDEA Impurities - Naseem Ahmad Charoo; Areeg Anwer Ali; Shailesh Kumar Buha; Ziyaur Rahman (AAPS PharmSciTech, 2019)

Antioxidant Potential of Indian Eggplant: Comparison Among White, Purple and Green Genotypes Using Chemometrics - Tanmay Kumar Koley; Shailesh Kumar Tiwari; Ananta Sarkar; Jyoti Nishad; Ashutosh Goswami; Bijendra Singh (Agricultural Research, 2019)

Nanopesticides: Opportunities in Crop Protection and Associated Environmental Risks - Shailesh Pandey; Krishna Giri; Rajesh Kumar; Gaurav Mishra; R. Raja Rishi (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Indirect Methods to Elucidate Water Flows and Contaminant Transfer Pathways through Meso-scale Catchments – a Review - Shailesh Kumar Singh; Roland Stenger (Environmental Processes, 2018)

Diversity of fungal endophytes in Typha latifolia (L.) and their lead biosorption activity - Samiksha Sharma; Kishan Lal Tiwari; Shailesh Kumar Jadhav (Euro-Mediterranean Journal for Environmental Integration, 2018)

Investigating Disease Controlling Ability of Brassica Volatiles and Their Compatibility with Trichoderma harzianum - Pramod Prasad; J. Kumar; Shailesh Pandey (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Metabolomics-assisted biotechnological interventions for developing plant-based functional foods and nutraceuticals - Arun Kumar; Kareem A. Mosa; Liyao Ji; Udaykumar Kage; Dhananjay Dhokane; Shailesh Karre; Deepa Madalageri; Neemisha Pathania (Critical Reviews in Food Science and Nutrition, 2018)

Linkage Disequilibrium Based Association and Inheritance of Blast Resistance in Improved Varieties and Landraces of Aromatic Rice - Balwant Singh; Shailesh Pandey; S. P. Singh; J. Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Haplotypic Diversity and Virulence of Xanthomonas oryzae pv. oryzae Population Infecting the First Superfine Aromatic Basmati Hybrid - Shailesh Pandey; Abhishek Bohra; Balwant Singh; Pramod Prasad; J. Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Biodegradation of Isoproturon by Bacillus pumilus K1 Isolated from Foothill Agroecosystem of North West Himalaya - Krishna Giri; Deep Chandra Suyal; Gaurav Mishra; Shailesh Pandey; Rajesh Kumar; Dinesh Kumar Meena; J. P. N. Rai (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Metabolo-transcriptome profiling of barley reveals induction of chitin elicitor receptor kinase gene (HvCERK1) conferring resistance against Fusarium graminearum - Shailesh Karre; Arun Kumar; Dhananjay Dhokane; Ajjamada C. Kushalappa (Plant Molecular Biology, 2017)

Use of remote sensing, GIS and C++ for soil erosion assessment in the Shakkar River basin, India - Rupesh Jayaram Patil; Shailesh Kumar Sharma; Sanjay Tignath; Aribam Priya Mahanta Sharma (Hydrological Sciences Journal, 2017)

Nonparametric catchment clustering using the data depth function - Shailesh Kumar Singh; Hilary McMillan; András Bárdossy; Chebana Fateh (Hydrological Sciences Journal, 2016)

Long-term Streamflow Forecasting Based on Ensemble Streamflow Prediction Technique: A Case Study in New Zealand - Shailesh Kumar Singh (Water Resources Management, 2016)

A genome-scale integrated approach aids in genetic dissection of complex flowering time trait in chickpea - Hari D. Upadhyaya; Deepak Bajaj; Shouvik Das; Maneesha S. Saxena; Saurabh Badoni; Vinod Kumar; Shailesh Tripathi; C. L. L. Gowda; Shivali Sharma; Akhilesh K. Tyagi; Swarup K. Parida (Plant Molecular Biology, 2015)

Modeling Storm Surge and its Associated Inland Inundation Extent Due to Very Severe Cyclonic Storm Phailin - T. Srinivasa Kumar; P.L.N. Murty; M. Pradeep Kumar; M. Krishna Kumar; J. Padmanabham; N. Kiran Kumar; S.C. Shenoi; M. Mohapatra; Shailesh Nayak; Prakash Mohanty (Marine Geodesy, 2015)

Design and Optimization of Curcumin–HPβCD Bioadhesive Vaginal Tablets by 23 Factorial Design: In Vitro and In Vivo Evaluation - Umme Hani; H. G. Shivakumar; Atul Srivastava; Nawaz Mahammed; Shailesh Thirumaleshwar; Naga Sravan kumar Varma; Rudra Vaghela; Chetan G. Shinde; M. P. Gowrav (Journal of Pharmaceutical Innovation, 2015)

Dominance of cyanobacterial and cryptophytic assemblage correlated to CDOM at heavy metal contamination sites of Gujarat, India - Shailesh Kumar Patidar; Kaumeel Chokshi; Basil George; Sourish Bhattacharya; Sandhya Mishra (Environmental Monitoring and Assessment, 2015)

Stress mitigating and growth enhancing effect of dietary tryptophan in rohu (Labeo rohita, Hamilton, 1822) fingerlings - Prem Kumar; Shailesh Saurabh; A. K. Pal; N. P. Sahu; A. R. T. Arasu (Fish Physiology and Biochemistry, 2014)

DNA typing and virulence determination of Xanthomonas oryzae pv. oryzae population for the management of bacterial leaf blight of rice in Udham Singh Nagar, India - Shailesh Pandey; Balwant Singh; J. Kumar (European Journal of Plant Pathology, 2014)

Beta-glucan: an ideal immunostimulant in aquaculture (a review) - D. K. Meena; Pronob Das; Shailesh Kumar; S. C. Mandal; A. K. Prusty; S. K. Singh; M. S. Akhtar; B. K. Behera; Kundan Kumar; A. K. Pal; S. C. Mukherjee (Fish Physiology and Biochemistry, 2013)

Comparative antibacterial activity of a novel semisynthetic antibiotic: etimicin sulphate and other aminoglycosides - Manu Chaudhary; G. Kesava Naidu; Shailesh Kumar; Anurag Payasi (World Journal of Microbiology and Biotechnology, 2012)

Improving the calibration strategy of the physically-based model WaSiM-ETH using critical events - Shailesh Kumar Singh; Jiaying Liang; András Bárdossy (Hydrological Sciences Journal, 2012)

Binning algorithm for high-resolution IRS-P4 OCM chlorophyll image - Prince Prakash; T. Srinivasa Kumar; S. H. Rahman; Shailesh Nayak (International Journal of Remote Sensing, 2012)

Identification of hot spots and well managed areas of Pichavaram mangrove using Landsat TM and Resourcesat—1 LISS IV: an example of coastal resource conservation along Tamil Nadu Coast, India - T. Srinivasa Kumar; R. S. Mahendra; Shailesh Nayak; K. Radhakrishnan; Kali C. Sahu (Journal of Coastal Conservation, 2012)

Arching in Inclined and Vertical Mine Stopes - Shailesh Singh; Sanjay Kumar Shukla; Nagaratnam Sivakugan (Geotechnical and Geological Engineering, 2011)

Variation in atmospheric aerosol properties over a tropical urban region associated with biomass-burning episodes – a study using satellite data and ground-based measurements - Anu Rani Sharma; Shailesh Kumar Kharol; K. V. S. Badarinath (International Journal of Remote Sensing, 2011)

Characterization of aerosol optical depth, aerosol mass concentration, UV irradiance and black carbon aerosols over Indo-Gangetic plains, India, during fog period - K. V. S. Badarinath; Shailesh Kumar Kharol; T. R. Kiran Chand; K. Madhavi Latha (Meteorology and Atmospheric Physics, 2011)

Development of a New Comprehensive Ocean Atlas for Indian Ocean utilizing ARGO Data - B. Prasad Kumar; Rahul Barman; S. K. Dube; P. C. Pandey; M. Ravichandran; Shailesh Nayak (International Journal of Climatology, 2010)
The World Ocean Atlas (WOA), also termed ‘Levitus Climatology’, is a global ocean climatology containing monthly, seasonal and annual means of temperature (T) and salinity (S) fields at standard ocean depths. The monthly climatology for T and S is available for standard depths up to 1000 m. The database used in the preparation of this climatology (WOA) are historical records of Conductivity, Temperature and Depth (CTD) casts and other available marine observations collected in the past. The methodology used in preparation of this WOA is objective analysis which is essentially non‐synoptic and widely scattered in the space domain. We understand that ARGO data has so far not been blended with WOA, nor has its impact for improving WOA climatology been attempted. Presently, with the wealth of marine data from ARGO profilers in the Indian Ocean, we propose a new approach to reconstruct T and S fields optimally utilizing the ARGO data. Here we develop a new model using Delaunay Tessellation with QHull algorithm delivering three‐dimensional T and S fields from a non‐uniform scattered database up to a depth of 1000 m. For gaps in a data‐sparse region, we use all available quality‐checked Ocean Station Data (OSD) and Profiling Float Data (PFL) information on T and S, in addition to the existing ARGO data. The initiative here was to replace WOA data points with realistic information from ARGO and in situ data, thereby producing a new climatology atlas. We demonstrate the robustness of our approach, and the final climatology on T and S is better compared with the existing state‐of‐the‐art WOA. The advantage of the proposed methodology is the scope of improving the ocean atlas with the addition of more ARGO data in the near future. The clustered approach in modelling enables ocean parameter retrieval in geometrically disconnected regions with an option for hot restart. We believe that the new climatology will benefit the research community immensely. Copyright © 2009 Royal Meteorological Society

Effect of water stress on carbon isotope discrimination and Rubisco activity in bread and durum wheat genotypes - Shailesh Kumar; Bhupinder Singh (Physiology and Molecular Biology of Plants, 2009)

Variations in CO, O3 and black carbon aerosol mass concentrations associated with planetary boundary layer (PBL) over tropical urban environment in India - K. V. S. Badarinath; Anu Rani Sharma; Shailesh Kumar Kharol; V. Krishna Prasad (Journal of Atmospheric Chemistry, 2009)

Variation in aerosol properties over Hyderabad, India during intense cyclonic conditions - K. V. S. Badarinath; Shailesh Kumar Kharol; V. Krishna Prasad; D. G. Kaskaoutis; H. D. Kambezidis (International Journal of Remote Sensing, 2008)

Studies on aerosol properties during ICARB-2006 campaign period at Hyderabad, India using ground-based measurements and satellite data - K. V. S. Badarinath; Shailesh Kumar Kharol (Journal of Earth System Science, 2008)

Influence of natural and anthropogenic activities on UV Index variations – a study over tropical urban region using ground based observations and satellite data - K. V. S. Badarinath; Shailesh Kumar Kharol; V. Krishna Prasad; Anu Rani Sharma; E. U. B. Reddi; H. D. Kambezidis; D. G. Kaskaoutis (Journal of Atmospheric Chemistry, 2008)

Effect of synoptic meteorological conditions on aerosol properties over urban environment: A study over tropical urban region of Hyderabad, India - Shailesh Kumar Kharol; K. V. S. Badarinath (Acta Geophysica, 2007)

Regional alterations of brain biogenic amines and GABA/glutamate levels in rats following chronic lead exposure during neonatal development - M. V. Shailesh Kumar; T. Desiraju (Archives of Toxicology, 1990)